Calling for Nexus Thinking in Africa's Energy Planning - Lucia de Strasser (Fondazione Eni Enrico Mattei (FEEM), 2017)
The simultaneous achievement of the sustainable development goals (SDGs) is, to say the least, challenging. In a situation of increasing and multiple demands over limited resources, pursuing each goal separately could lead to increased competition. The situation in Africa is particularly problematic, as the continent lags behind all others in terms of quality and quantity of infrastructure and counts the highest shares of population living in poverty and without access to food, safe water, and energy. At the same time, natural resources are under increasing pressure from population growth, environmental degradation, and climate change. Given the entity of the challenge, finding synergies and strengthening coordination across sectors will be crucial and the energy sector has an important role to play. As recognized in the Agenda 2030, the energy sector holds the key to many aspects of development, however no energy solution (albeit green or synergetic) should be casually labelled as a nexus solution. This could be deceiving also because of the ambiguities that surround the concept of nexus. In order to give concrete insights to policy makers, this paper proposes a pragmatic approach to the nexus that allows on one hand to detect areas where cooperation needs to be strengthened, on the other to explore the nexus potential of energy solutions. This is in line with a view of the nexus as a way of thinking, which can apply both at the level of policy making and in the actual implementation of projects. We will give three concrete examples to improve energy access at different levels: multipurpose hydropower for large-scale electricity production, solar pumps for irrigation in farms, and efficient cookstoves in households. These can catalyse much needed action in other areas (notably water supply, agriculture, and forestry) but realizing their potential requires stronger cooperation and coordination across sectors. Moreover, their successful implementation requires an honest and thorough assessment of the local context in terms of constraints as well as opportunities.
Keywords: O13; O55; Q49; 330; Africa; Energy Access; Nexus Approach; Resource Security; Environmental Sustainability; Water Management; Agriculture; SDGs